Castaway kid - Mitchell, R. B. (Robert Bivings), 1954- (Carol Stream, Ill. : Tyndale House Publishers, 2007)
R. B. Mitchell reflects on his life being raised in an orphanage and discusses how his relationship with God helped him survivor many challenges, reconnect with his family, and become a successful businessman.
"Focus on the Family."
Includes bibliographical references (p. [245]-249).
Adult
Adult
Keywords: Mitchell, R. B. -- 1954-; Orphans -- Illinois -- Biography; Children -- Institutional care -- Illinois -- Case studies; Parental rejection -- Illinois -- Case studies; Adult children of dysfunctional families -- Biography; Mitchell, R. B. -- 1954-; Orphans -- Illinois -- Biography; Children -- Institutional care -- Case studies; Parent-child relationship -- Case studies; Adult children of dysfunctional families -- Biography